Associations Between Australian Pseudoscorpions and Ants - Deborah C. Cole; Mark A. Elgar; Mark S. Harvey (Psyche: A Journal of Entomology, 1994)
The distribution of three species of pseudoscorpions, found under the bark of blue gum Eucalyptus globulus, is closely correlated with the presence of three species of ants. Marachernes bellus is never found on trees without Anonychomyrma sp. near foetens, and Protochelifer victorianus and Paraustrochernes victorianus are more commonly found on trees with Technomyrmex jocosus and/or Tapinoma minutum. The distribution of another pseudoscorpion, Conicochernes sp., is not influenced by the presence of these ants. Observations of the behavior of these pseudoscorpions indicate that at least some species may be specialist predators of ants.